Year after year: Recurrent Toxocara vitulorum infections in American bison (Bison bison) calves in a zoo - David Ebmer; Maria Sophia Unterköfler; Zoë Tess Lara Lindhorst; Perrine Keiser; Simone Haderthauer; Stephan Hering-Hagenbeck; Anja Joachim (International Journal for Parasitology: Parasites and Wildlife)
Toxocara vitulorum (Nematoda: Ascaridida) is a common parasite of cattle and buffaloes in tropical and subtropical regions and the causative agent of toxocarosis in calves. In Europe, sporadic infections have been reported in cattle, but also in bovines held at zoological gardens. Here, we report T. vitulorum infections in a herd of American bison (Bison bison) kept at the Vienna Zoo, Austria, which occurred in 2023 and 2024. After the first case in a seven-week-old calf in July 2023, another case in a five-week-old calf was diagnosed in May 2024, both of them detected by coproscopy and fecal discharge of adult worms after anthelminthic treatment. The calves originated from two different mothers imported to the zoo in 2014 from the Czech Republic and 2012 from Germany respectively. Both calves showed diarrhea and fecal soiling of the anal region prior to fecal analysis. Two intramuscular administrations of ivermectin (0.2 mg/kg bodyweight, two-week interval) caused the passing of up to 39 cm long gravid female worms, resulted in the cessation of egg shedding and improved fecal consistency. Morphological and molecular identification confirmed infections with T. vitulorum. Additionally, another calf, born in May 2024 from the mother of the calf that was T. vitulorum-positive in 2023, showed periods of diarrhea. Due to difficulties in taking individual samples, no definitive diagnosis of T. vitulorum infection could be made, however, the animal was also treated and clinically improved afterwards. Besides T. vitulorum, Eimeria spp. were detected in all samples and Giardia duodenalis genotype E in two samples in 2024. This case series highlights the possibility of unnoticed parasite introductions into zoological gardens via animals infected with resting parasite stages, and demonstrates the importance of regular individual parasitological analysis in bovine zoo animals during the first weeks after birth.